2019
DOI: 10.1021/acssuschemeng.9b04567
|View full text |Cite
|
Sign up to set email alerts
|

A Star Polycation Acts as a Drug Nanocarrier to Improve the Toxicity and Persistence of Botanical Pesticides

Abstract: The excessive use of chemical pesticides brings many environmental problems. Botanical pesticides seem to be a good alternative to control pests, but their slow action and lack of residual action constrain their further application. Here, we developed a star polycation (SPc) as the drug nanocarrier that could combine matrine into a complex to decrease its particle size to the nanoscale. The combination of SPc and matrine increased the zeta potential and the noncovalent molecular interaction, such as hydrogen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 52 publications
11
96
0
Order By: Relevance
“…Incorporation of nanoparticles into conventional insecticides can be used to improve AI solubility 18, 28 . Our previous study confirmed a smaller particle size for matrine/SPc complex compared with matrine, suggesting that SPc could be used as an insecticide adjuvant to decrease the particle size of insecticides to the nanoscale and improve water‐solubility 39 . In the current study, pure thiamethoxam was used to determine the interaction between insecticide and nanocarrier.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Incorporation of nanoparticles into conventional insecticides can be used to improve AI solubility 18, 28 . Our previous study confirmed a smaller particle size for matrine/SPc complex compared with matrine, suggesting that SPc could be used as an insecticide adjuvant to decrease the particle size of insecticides to the nanoscale and improve water‐solubility 39 . In the current study, pure thiamethoxam was used to determine the interaction between insecticide and nanocarrier.…”
Section: Discussionmentioning
confidence: 51%
“…The thiamethoxam was able to spontaneously assemble with SPc through electrostatic interaction, which might be attributed to interaction between the positively charged tertiary amine in the side chain of SPc and negatively charged nitro group in thiamethoxam. Complexation of SPc with matrine or G2 with thiamethoxam was different and both were non‐covalent molecular interactions, such as hydrogen bonds and hydrophobic interactions 37, 39 . SPc could be complexed with exogenous substances through different interaction mechanisms, which was beneficial for extending its application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al (2020b) applied this star polycation as a highly efficient gene carrier, and the dsRNA/nanoparticle formulation targeting V-ATPaseD and chitin synthase1 genes was directly sprayed onto soybean seedlings infected with Aphis glycines, resulting in a good control effect (mortality rate: 78.5%). This star polycation can also be used as a pesticide adjuvant to improve the toxicity and persistence of botanical pesticides (Yan et al, 2019). Sprayable RNAibased products can be easily applied as chemical pesticides, and the application of this nanoparticle to deliver pesticide and dsRNA simultaneously may be a good option for foliar spray.…”
Section: Cationic Dendrimersmentioning
confidence: 99%
“…Each repeated branched layer represents a higher generation molecule, and the dendrimer surface can be engineered to build a variety of functions (Boas & Heegaard, 2004; Chen & Yin, 2014). Modified dendrimers are not only used for drug delivery, but are also attractive means of delivering plasmid DNA, antisense oligonucleotides, and siRNA/dsRNA because of the high density of positive charges on their surfaces (Perez‐Martinez et al ., 2012; Yan et al ., 2019). The high water solubility of cationic dendrimers enables them to be good nucleic acid nanocarriers during biological applications (Sun et al ., 2016).…”
Section: Variety and Characteristics Of Nanoparticles For Dsrna/sirnamentioning
confidence: 99%